Experimental evaluation and empirical modelling of palm oil mill effluent steam reforming - Ng, Kim Hoong; Cheng, Yoke Wang; Lee, Zhan Sheng; Khan, Maksudur R.; Lam, Su Shiung; Cheng, C. K. (Elsevier Ltd, 2018)
The current work describes a novel application of steam reforming process to treat palm oilmill effluent (POME), whilst co-generating H2-rich syngas from the treatment itself. The effects of reaction temperature, partial pressure of POME and gas-hourly-space-velocity (GHSV) were determined. High crystallinity 20 wt%Ni/80 wt%Al2O3 catalyst with smooth surface was prepared via impregnation method. Baseline runs revealed that the prepared catalyst was highly effective in destructing organic compounds, with a two-fold enhancement observed in the presence of 20 wt% Ni/80 wt%Al2O3 catalyst, despite its low specific surface area (2.09 m2 g−1). In addition, both the temperature and partial pressure of POME abet the COD reduction. Consequently, the highest COD reduction of 99.7% was achieved, with a final COD level of 73 ± 5 ppm from 27,500 ppm, at GHSV of 40,000 mL/h.gcat and partial pressure of POME equivalent to 95 kPa at 1173 K. In terms of gaseous products, H2 was found to be the major component, with selectivity ranged 51.0%–70.9%, followed by CO2(17.7%–34.1%), CO (7.7%–18.4%) and some CH4 (0.6%–3.3%). Furthermore, quadratic models with high R2-values were developed.